Hubungan antara Kontrol Diri dengan Gaya Hidup Hedonisme Remaja di Kafe - Elsa Irmeiyanti Hersika; Krisnova Nastasia; Harri Kurniawan (Psyche 165 Journal, 2020)
This study aims to determine the relationship between self-control and adolescent hedonism lifestyle in Padang City with a population of 98,884 adolescents and as many as 100 people while the data collection technique uses incidental sampling. Based on the hypothesis test conducted shows that there is a strong relationship between the relationship between self control and adolescent hedonism lifestyle in the city of Padang which is shown by the correlation coefficient rxy = -0,824 with a significant level of correlation p = 0,000. A positive value on the correlation coefficient shows the relationship between self control and the adolescent hedonism lifestyle in Padang City, meaning that the higher the self-control of adolescents the lower the hedonism lifestyle and conversely the more self-control the lower the hedonism lifestyle. The amount of effective contribution (Rsquare) of the hedonism lifestyle variable to self control is 68%, which means that hedonism lifestyle has a contribution of 68% to self control while 32% is influenced by other factors.